2023
DOI: 10.1021/acs.jproteome.2c00682
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Lipidomic Workflow for Multicohort Population Phenotyping Using Stable Isotope Dilution Targeted Liquid Chromatography-Mass Spectrometry

Abstract: Dysregulated lipid metabolism underpins many chronic diseases including cardiometabolic diseases. Mass spectrometry-based lipidomics is an important tool for understanding mechanisms of lipid dysfunction and is widely applied in epidemiology and clinical studies. With ever-increasing sample numbers, single batch acquisition is often unfeasible, requiring advanced methods that are accurate and robust to batch-to-batch and interday analytical variation. Herein, an optimized comprehensive targeted workflow for pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…However, we provide evidence that using such an approach can provide value in the biological validation of phenotypes where matched biofluids are not available, indicating that biofluids independently collected using nonmatched protocols (plasma vs serum) may still serve as a valuable validation set to corroborate phenotypic trends and signatures. This builds upon our previous work where we have demonstrated that targeted phenotyping workflows can be robust to different sampling conditions, including blood collection type and degrees of hemolysis when using targeted lipidomic 70 and lipoprotein phenotyping. 71 These findings justify that there remains value in validating biomarker signatures in cohorts in which samples may have been collected or treated differently, withstanding that the methodology is robust to external influences.…”
Section: Discussionmentioning
confidence: 83%
“…However, we provide evidence that using such an approach can provide value in the biological validation of phenotypes where matched biofluids are not available, indicating that biofluids independently collected using nonmatched protocols (plasma vs serum) may still serve as a valuable validation set to corroborate phenotypic trends and signatures. This builds upon our previous work where we have demonstrated that targeted phenotyping workflows can be robust to different sampling conditions, including blood collection type and degrees of hemolysis when using targeted lipidomic 70 and lipoprotein phenotyping. 71 These findings justify that there remains value in validating biomarker signatures in cohorts in which samples may have been collected or treated differently, withstanding that the methodology is robust to external influences.…”
Section: Discussionmentioning
confidence: 83%
“…Plasma lipid analysis was performed by ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) using a Exion UHPLC system coupled to a QTRAP 6500+ mass analyzer (Sciex Concord, CA) from a previously published method. 34 In brief, plasma samples (10 μL) were thawed at 4 °C and combined with 90 μL of stable isotopically labeled internal standards diluted in isopropyl alcohol for extraction, utilizing a Biomek i5 liquid handling system for the preparation (Beckman Coulter, Mount Waverley, Victoria 3149, Australia). Samples were chilled and centrifuged for 15 min at 14000 g before 50 μL of supernatant was transferred into a 350 μL 96-well plate for analysis (Eppendorf, Macquarie Park, NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…25 Ryan et al describe the robust optimization of a clinical analytical pipeline to quantify over 1000 lipid species from plasma and serum using internal standards labeled with stable isotopes (SIL-IS) and targeted mass spectrometry. 26 Finally, two of the computational pipelines described above for deep proteomics were applied to patient samples and shown to significantly improve our ability to detect genomic variants 7 and glycosylated biomarkers. 8 Such technical improvements on both the LC-MS side and the computational analysis of the resulting data sets have the potential to support personalized medicine on a large-scale.…”
Section: Clinical Mass Spectrometry Applicationsmentioning
confidence: 99%
“…Spray stability is an important parameter to control when high reproducibility and depth of analysis are of paramount importance, such as for analyzing multiple patient samples . Ryan et al describe the robust optimization of a clinical analytical pipeline to quantify over 1000 lipid species from plasma and serum using internal standards labeled with stable isotopes (SIL-IS) and targeted mass spectrometry . Finally, two of the computational pipelines described above for deep proteomics were applied to patient samples and shown to significantly improve our ability to detect genomic variants and glycosylated biomarkers .…”
mentioning
confidence: 99%